Defining Disability: Reviewing the Construct of Special Education - Haley Clark (Canadian Society for Studies in Education, 2023)
It is common within Ontario's educational context to hear the term 'special needs' or 'special education'. However, the relationship between language, definitions, and discourse in the treatment of students with disabilities in Ontario's elementary and secondary schools is understudied. Drawing on an extensive body of literature from the sociology of education, disability studies, and special needs education, this paper aims to recognize the profound influence of language and labels on societal perceptions and the treatment of students with disabilities. While investigating the historical definitions of disability, literature in this area highlights the continuous debate and inconsistencies surrounding terminology in academic and educational contexts. By focusing on the often-used term "special needs", this research examines the potential negative impact of this label on reinforcing ableism and prejudices for students with disabilities. Moreover, language, definitions, and discourse have the power to shape perceptions and, if not used thoughtfully, may inadvertently perpetuate negative stereotypes and hinder students' academic and social development. Therefore, educational terminology should be altered to reflect equitable decision-making and dignity throughout supports for students.